Questioni di rigore nella ricerca-azione educativa - Massimo Baldacci (LED Edizioni Universitarie, 2013)
Questions of Rigor in Educational Action-Research The paper examines the problems of rigour linked to the use of qualitative methods in pedagogical action-research. Firstly the idea of rigour in pedagogical research is considered. In this regard, the concept of rigour is traced back to three issues that, although different, are also related: rigour as severity of methods, as scrupulousness in their application and as appropriateness of the approach to the problem dealt with in the study. Then some questions of rigour in action-research based on qualitative methods are examined. In this regard, it is shown that, despite the fact that qualitative methods may be characterized by severe logics which are coherent with their internal epistemology, methodological limits are often found whose roots cannot be traced back exclusively to amateurishness, but may also be due to the cultural predominance assumed by the hermeneutics paradigm, which is capable of inducing a unilateral supremacy when interpreting data. Finally, some general guidelines are formulated for a rigorous approach to qualitative action-research. In this regard, several theoretical and methodological antinomies are compared in an attempt to identify a way of resolving them rationally with respect to action-research, in order to assure an objective epistemological profile to this study approach. The following antinomies are examined: objectivity/subjectivity; realism/constructivism, hermeneutics/pragmatism.